(3GdYeOI aj UfGYI GdLQGMIs - (3CHh GdaQL Hf ehab GdOjf jYbhH Hf GSMb,J (B685 (3g` s ((3LHQGjjd Hf ejNGFjd GdTgjQ GdScQ hL s)
(3ChdgG (B:s
(3hHYO abO TcG Edi HYV LQGjMjI ReGffG gPG bdI EgJeGe CQHGH gPG Gdaf aCLHJg Edi Pdc eSJYjfkG HGddg JYGdi Ld PcQI hJbOS GSeg hbO hSejJg GdYeOI ai UfGYI GdLQGMI hQJHJg ai YTQjf ebGdg s
(3BNQgG (B:s
(3hjLYd ai TeS MGQI KdGKhf jhekG , hjMQc cd jhe , hjLYd ai EfGA eQLM hjSJYed Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ YfGhjjf GdebGdGJ HNW YQjV hYfGhjjf GdaUhd HGdeOGO GdCMeQ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdWHs